STRATEGI PEMILIK BISNIS STARTUP DI INDONESIA HADAPI PANDEMI COVID-19 - Amalia Tiffany; Annisa Yuniar; Axel Febrian; Jennifer Austeen; Liony Suryaputra; Michelle Hannah; Timotius Kevin; Wendy Bagas (Universitas Ciputra Surabaya, 2020)
Basically a startup is a company that runs under 5 years or can be called a company that has just been started. But now the definition of the meaning of a startup has turned into a business that is just running and applying technological innovation to solve a problem in society. And now Indonesia has many startups that are pioneering in various fields ranging from e-commerce, logistics, transportation, health to education. However, since the Covid-19 pandemic hit Indonesia, the impact began to be seen in all economic sectors, including startups. Most or 42.5% of digital startups are in bad condition due to Covid-19. So this study aims to examine the strategy of startup owners to deal with the Covid-19 pandemic. This study uses a phenomenological qualitative method to describe how humans experience the Covid-19 virus phenomenon. The results show that business owners can provide and increase brand awareness of their products or services. By maximizing management on social media, startup companies will be able to communicate values to their companies that they consider can also help or facilitate the community in the midst of the COVID-19 pandemic. Keywords: startup, company, covid-19.